Reliable integration of a high performance multi-chip half-bridge SiC power module - Mouawad, Bassem; Li, Jianfeng; Castellazzi, Alberto; Johnson, Christopher Mark (2016)
Silicon carbide (SiC) devices have been adopted to push the boundaries further in terms of power density, conversion efficiency, switching speed or thermal capability. To have the benefit of such semiconductors, new packaging should be developed to meet all the advantages. In this paper, we present a reliable integrated concept of a new packaging solution for multi-chip SiC devices aiming to have a very low parasitic inductance in order to have high switching frequencies and ensure a good reliability for long-term operation.